TINGKAT KONSUMSI ENERGI, AKTIVITAS FISIK DAN KESEGARAN JASMANI PADA POSISI (TOSSER DAN SMASHER) ATLET BOLA VOLI - Dwi Ayu Novitasari; M. Zen Rahfiluddin; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Physical health is the ability of human’s body to perform physical activity without experiencing fatigue. Tosser, as well as smasher, has important roles in the game, in which tosser works as a regulator of the game, receiver of the second ball and then assist the ball to smasher to attack the opponent, in order to have more point and to win. Volleyball players need more energy and endurance so they can feel tireless. Tosser has motion activity in the field more than other players and better endurance. More motion activity requires more energy intake to created optimal physical health. The purpose of this research is to determine the differences level of energy consumption, physical activity and physical health on each position (tosser and smasher) of volleyball athlete. The type of this research is a comparative study using cross-sectional approach. The population is all tosser and smasher on Kudus’s volleyball clubs. The sample of 17 people for each group tosser and smasher use purposive sampling, the sample was selected according to research criteria so characteristics of the population can be well represented. Independent T-test was used for analysis level of energy consumption, meanwhile, Mann-Whitney U test was used for analysis physical activity and physical health. The results showed that there was no difference level of energy consumption (p=0,943), there were differences physical activity (p=0,001) and physical health (p=0,001). This research suggests that increasing energy consumption is obviously needed for an athlete. Sports nutrition consultation is also needed for coaches and parents.